Executive Women and their Bodies: Marks of Aging - Vieira, Renata Barbosa de Assis; Cepellos, Vanessa (Organizações & Sociedade, 2022)
The present article regards executive women and their aged bodies. The population aging phenomenon and old age feminization are global factors. Based on the literature about the sociohierarchized body, white, thin, male bodies are privileged in organizations. The aim of the present study is to investigate how executive women experience their aged bodies within the organizational context. The discussion emerges as relevant, since there are few studies related to aging women; studies on body-related factors are even scarcer, a fact that shines light on a theoretical gap. In total, twenty semi-structured interviews were carried out with women in the age group 40 years, or older, who act or had acted in several market segments in the country. The research allowed concluding that, in addition to challenges, choices and doubts faced on a daily basis throughout their professional journey, women have to live with a body-under-decay process, a heavy, tired, slow, stiff, limiting and less-attractive-to-the-eye body. The present study has revealed that besides gender, age also matters in organizations, nowadays. The bodies of older women are less valued and seem to have to occupy underprivileged positions in social hierarchy. In order to mitigate losses, women seek aesthetic procedures, change their eating habits and exercise to disguise the aging process.